2006
DOI: 10.1017/s0043933906001127
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the use of phosphorus sources in growing meat ducks

Abstract: Optimal utilisation of limited phosphate resources in animal feeding requires detailed knowledge of both the requirement for available phosphorus (P), and the availability of P from relevant feed ingredients. In growing ducks, the P concentration of gained body weight and the inevitable P losses voided determine the requirement for available P. The concentration of available P needed in the diet then depends on the feed conversion ratio. Plant and mineral feedstuffs contribute to the available P content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Phosphorus concentrations were calculated to be slightly below the estimated requirement, as 145 suggested by Rodehutscord (2005). The calculated concentrations of ME were 12.2 and 12.5 146 MJ/kg in phase one and two, respectively.…”
Section: Growth Study 141mentioning
confidence: 82%
See 1 more Smart Citation
“…Phosphorus concentrations were calculated to be slightly below the estimated requirement, as 145 suggested by Rodehutscord (2005). The calculated concentrations of ME were 12.2 and 12.5 146 MJ/kg in phase one and two, respectively.…”
Section: Growth Study 141mentioning
confidence: 82%
“…Average annual growth in duck meat production between 1998 and 2003 was 3% in Europe 36 and 6% worldwide (FAO, 2005). Yet, effective nutrition of ducks must not only meet the 37 animal's requirements for growth and health; with particular relevance in the case of P, 38 avoiding excessive intake and minimising excretion is also relevant for economic and 39 ecological reasons (Rodehutscord, 2005). Consequently, the role of phytase as a feed 40 supplement in ducks has been of increasing interest, especially the use of a 3-phytase derived 41 from the Aspergillus niger gene (Farrell et al, 1993;Martin et al, 1998;Orban et al, 1999;42 Attia, 2003;Wendt et al, 2003).…”
mentioning
confidence: 99%
“…Mineral concentration in body weight is quantitatively the most important (Rodehutscord, 2006), but it can be studied with reasonable effort by a whole body analysis.…”
mentioning
confidence: 99%
“…Many studies have indicated that Ca and P utilization in poultry is affected by nutritional factors, such as Ca-P ratio and the levels of phytase and VD 3 additions ( Rodehutscord, 2006 ). For dietary Ca-P ratio, Rodehutscord and Dieckmann (2005) and Rush et al.…”
Section: Introductionmentioning
confidence: 99%